Exercise interventions and epidemiological approaches in obesity - Kuk, Jennifer (Henry Stewart Talks, 2026)
Obesity is caused by long-term positive energy balance, Caloric intake in relation with BMI, Obesity treatment pyramid, Long-term weight loss research interventions, Surgical vs. non-surgical interventions, Obesity in relation with health risk factors